The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpls.2020.01270
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Therapy: Could a Chlorophyll Derivative Promote Cellular Accumulation of Zn2+ Ions to Inhibit SARS-CoV-2 RNA Synthesis?

Abstract: MEDICINAL USES OF CHLOROPHYLL DERIVATIVES A range of tetrapyrrole derivatives are in development for their observed cytotoxicity (Kang et al., 2018; Singh et al., 2019). Non-toxic, water-soluble chlorophyll derivative compounds are a popular dietary supplement among health-conscious members of high-income countries. Many organometallic compounds derived from chlorophyll a or b are approved for human consumption. For instance, sodium copper chlorophyllin is promoted for both its anti-bacterial and anti-viral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…It is interesting that Pba (or highly related compounds such as pyroPba) has been isolated from different plant species and different organisms, including marine algae ( 38 ), rendering Pba a very attractive antiviral due to its high availability. Moreover, it has been postulated that Pba can transport a metal ion like zinc inside the cell and that zinc can inhibit viral replication ( 39 ), which might be another advantage to using these molecules as antivirals. In our study, it was confirmed that neither natural nor commercial Pba used in our experiments contained a metal ion, so future studies should be performed with zinc Pba to demonstrate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that Pba (or highly related compounds such as pyroPba) has been isolated from different plant species and different organisms, including marine algae ( 38 ), rendering Pba a very attractive antiviral due to its high availability. Moreover, it has been postulated that Pba can transport a metal ion like zinc inside the cell and that zinc can inhibit viral replication ( 39 ), which might be another advantage to using these molecules as antivirals. In our study, it was confirmed that neither natural nor commercial Pba used in our experiments contained a metal ion, so future studies should be performed with zinc Pba to demonstrate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, organometallic compounds such as sodium copper chlorophyllin synthesized from chlorophyll show antibacterial and antiviral activity [113] , [114] . An enhanced level of antiviral activities can be achieved using nanomaterials, as discussed in the next section.…”
Section: Antiviral Strategies Against Coronavirusesmentioning
confidence: 99%
“…58 Chlorophyll derivatives have proven antiviral activity against SARS-CoV-2 virus. 59 Chlorophyll A absorbs light in the violet-blue region (430-450 nm) and is a type II PI that can initiate the free radical photopolymerization of methyl methacrylate, to produce cross-linked polymethyl methacrylate. 60…”
Section: Chlorophyllsmentioning
confidence: 99%